Pengaruh Waktu Maserasi Terhadap Aktivitas Antioksidan Ekstrak Daun Mundu (Garcinia dulcis (Roxb.) Kurz) - Widodo, Setyo; Yusa, Ni Made; Timur Ina, Putu (Jurnal Ilmu dan Teknologi Pangan (ITEPA); Vol 10 No 1 (2021): Jurnal ITEPA, 2021)
The research aimed to find effect of maceration time on antioxidant activity of mundu leaf extract and to know the best maceration time with highest antioxidant activity of mundu leaf extract. This study used a completely randomized design with treatment of maceration time 6 level: 12 hours, 24 hours, 36 hours, 48 ??hours, 60 hours, and 72 hours. The experiment was repeated in three replication, so that 18 experimental units were obtained. The variabels observed ware extraction yield, total tannin, total flavonoids, total phenol, and antioxidant activity. The data obtained were analyzed by ANOVA and if the treatment had significant effect followed by Duncan test. The result showed were maceration time has significant effect on extraction yield, total tannin, total flavonoids, total phenol, and antioxidant activity of mundu leaf extract. The best treathment was 24 hours with extraction yield was 24.67 %, total tannin was 133.04 mg.TAE/g, total flavonoids was 364.36 mg.QE/g, total phenol was 143.82 mg.GAE/g, and antioxidant activity was 86.89 % with  IC50 was 47.45 mg/L.